1977
DOI: 10.1037/0033-2909.84.4.690
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory interactions between appetitive and aversive stimuli.

Abstract: This article reviews the behavioral evidence that a stimulus of a given affective value will exert a central inhibitory influence on responding maintained by stimuli of the opposite affective value. The effects of aversive stimuli on appetitively motivated behavior and of appetitive stimuli on aversively motivated behavior are considered separately. The evidence for a true inhibitory action is evaluated in terms of three behavioral criteria: the summation, retardation, and counterconditioning tests. Special at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
124
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 115 publications
(126 reference statements)
10
124
0
Order By: Relevance
“…The results confirmed that participants had attached emotional relevance to the previously trained CI, this contributed to the way they rated stimuli and in consequence how they learned about the stimuli subsequently in comparison to novel stimuli (Dickinson & Pearce, 1977;Konorski, 1948;1967;Konorski & Szwejkowska, 1956). …”
Section: Discussionsupporting
confidence: 58%
“…The results confirmed that participants had attached emotional relevance to the previously trained CI, this contributed to the way they rated stimuli and in consequence how they learned about the stimuli subsequently in comparison to novel stimuli (Dickinson & Pearce, 1977;Konorski, 1948;1967;Konorski & Szwejkowska, 1956). …”
Section: Discussionsupporting
confidence: 58%
“…The decline in defensive behavior was accompanied by the development of an alimentary conditioned response, salivation, to the shock, suggesting that appetitive conditioning may be an important causal factor underlying the successful counterconditioning of aversive stimuli. Subsequently, outside the Russian literature (e.g., Marukhanyan, 1954), little attention has been paid to the counterconditioning of the responses elicited by unconditioned aversive stimuli despite the theoretical importance of the phenomenon for understanding appetitive-aversive interac-By contrast, the counterconditioning of conditioned, as opposed to unconditioned, defensive responses has been somewhat more intensively studied (see Dickinson & Pearce, 1977;Wilson & Davison, 1971, for recent reviews). For example, Scavio (1974) initially conditioned a defensive nictitating membrane response to an auditory CS with a paraorbital These experiments are based on a Masters thesis submitted by M. F. Dearing to the University of Sussex.…”
mentioning
confidence: 99%
“…By contrast, the counterconditioning of conditioned, as opposed to unconditioned, defensive responses has been somewhat more intensively studied (see Dickinson & Pearce, 1977;Wilson & Davison, 1971, for recent reviews). For example, Scavio (1974) initially conditioned a defensive nictitating membrane response to an auditory CS with a paraorbital These experiments are based on a Masters thesis submitted by M. F. Dearing to the University of Sussex.…”
mentioning
confidence: 99%
“…These considerations may explain why results using this procedure have been contradictory (Delprato & Jackson, 1973;Poppen, 1970). Also, as pointed out by Dickinson and Pearce (1977), the only experiment using this procedure that obtained a difference favoring the counterconditioning group (Poppen, 1970) changed the schedule for the baseline response from VI 60 sec in acquisition to consistent reward in test for the counterconditioning group, which could account for the difference between this group and the control group. Wilson and Dinsmoor (1970) trained rats to remain on a platform to avoid shock.…”
mentioning
confidence: 98%
“…Reviews of counterconditioning experiments (Dickinson & Pearce, 1977; Reid, 1973; Wilson & Davison, 1971) indicate that, when exposure to the This research was supported in part by the National Institute of Mental Health, Grant MH34119, to the first author. Reprints can be obtained from the first author, Department of Psychological Sciences, Purdue University, West Lafayette, Indiana 47907. feared cue is equated, most comparisons of counterconditioning and extinction have not found that counterconditioning reduces fear any better than does mere exposure to the feared cue.…”
mentioning
confidence: 99%